ANALISIS SOAL INTERNATIONAL JUNIOR OLYMPIADE (IJSO) SAINS (KIMIA) BERDASARKAN DIMENSI PROSES KOGNITIF DAN PENGETAHUAN - Yunita Yunita (Universitas Sultan Ageng Tirtayasa, 2017)
Abstract: This study aimed to describe the composition of the dimension of the cognitive process based on Bloom's Taxonomy revision questions from IJSO chemical Nigeria 2010, analyzing the mapping dimension of cognitive processes and dimensions of knowledge on the IJSO chemical concept in Nigeria 2010, and describes mapping of IJSO chemical question in Nigeria 2010 by senior high school competences. The method of research conducted qualitative descriptive. The technique begins with the completion of the stages do matter, then categorize into one of the six cognitive dimensions and four dimensions of knowledge. Problem is analyzed in this study of IJSO (Chemistry) Nigeria in 2010 with details of 10 Multiple Choice questions, Theoretical Test in the form of discourse, and 12 questions of Experiment Test. Based on the analysis, findings, and the discussion in this study, the composition of the dimension of the revised Bloom's taxonomy of cognitive processes considering the aspect (C1) 2.94%, to understand (C2) of 5.88%, apply (C3) 44.12), analyzing 32 , 35%, judging (C5) 14.71%, and creates 0%, while mapping the dimensions of cognitive processes and dimensions of 8.82% factual knowledge, conceptual knowledge and procedural knowledge 44.11% amounting to 47.06%. Based on analysis of the details of conformity competency in senior high school as follows, as much as 38.24% of the material in class X, XI A total of 50.00%, while 11.76% of class XII.   Abstrak: Peneltian ini bertujuan untuk mendeskripsikan komposisi dimensi proses kognitif Taksonomi Bloom revisi soal-soal IJSO kimia Nigeria 2010, menganalisis pemetaan dimensi proses kognitif dan dimensi pengetahuan pada soal IJSO kimia Nigeria 2010, dan mendeskripsikan pemetaan soal-soal IJSO kimia Nigeria tahun 2010 berdasarkan SK/KD SMA/MA. Metoda penelitian yang dilakukan deskriptif kualitatif. Teknik yang dilakukan diawali dengan penyelesaian tahapan soal, kemudian diklompokkan kedalam salah satu dari enam dimensi kognitif dan empat dimensi pengetahuan. Soal yang di analisis pada penelitian ini dari IJSO (Kimia) Nigeria tahun 2010 dengan rincian Multiple Choice 10 soal, Theoritical Test dalam bentuk wacana, dan Exprerimental Test 12 soal. Soal-soal tersebut sama dengan silabus di Indonesia sesuai kurikulum KTSP tingkat SMA. Berdasarkan hasil analisis data, temuan, dan pembahasan pada penelitian ini, komposisi dimensi proses kognitif taksonomi Bloom revisi aspek mengingat (C1) 2,94%, memahami (C2) 5,88%, mengaplikasi (C3) 44,12), menganalisa 32,35%, menilai (C5) 14,71%, dan mencipta 0%, sedangkan pemetaan dimensi proses kognitif dan dimensi pengetahuan faktual 8,82%, pengetahuan konseptual 44,11% dan pengetahuan prosedural sebesar 47,06%. Berdasarkan hasil analisis rincian kesesuaian SK/KD SMA sebagai berikut, sebanyak 38,24 % materi kelas X, Sebanyak 50,00% kelas XI, sedangkan kelas XII sebesar 11,76%.